2021
DOI: 10.3389/fmars.2021.624981
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Population-Level Effects of Anthropogenic Disturbance on a Marine Mammal Population

Abstract: The Population Consequences of Disturbance (PCoD) model is a conceptual framework used to assess the potential for population-level consequences following exposure of animals to a disturbance activity or stressor. This framework is a four-step process, progressing from changes in individual behavior and/or physiology, to changes in individual health, then vital rates, and finally to population-level effects. Despite its simplicity, there are few complete PCoD models available for any marine mammal species due … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…The most widespread use of dynamic bioenergetic models in the past decade has been in the context (either implicit or explicit) of assessing the long-term consequences of sublethal anthropogenic disturbance on individuals or populations under the PCoD framework, which has included applications to pinnipeds ( Goedegebuure et al, 2018 ; McHuron et al, 2017a , 2018 ), harbour porpoises Phocoena phocoena ( Gallagher et al, 2021a ; Harwood et al, 2020 ; Nabe-Nielsen et al, 2014 ; Nabe-Nielsen et al, 2018 ), delphinids ( Hin et al, 2019 ; New et al, 2013b ; Pirotta et al, 2014 ; Pirotta et al, 2015 , 2020 ; Reed et al, 2020 ; Williams et al, 2006 ), beaked whales ( New et al, 2013a ), baleen whales ( Braithwaite et al, 2015 ; Christiansen and Lusseau, 2015 ; Dunlop et al, 2021 ; Guilpin et al, 2020 ; McHuron et al, 2021 ; Pirotta et al, 2018a , 2019 , 2021 ; Riekkola et al, 2020 ; van der Hoop et al, 2017 ; Villegas-Amtmann et al, 2015 ; Villegas-Amtmann et al, 2017 ), small- to medium-sized odontocetes ( Noren et al, 2017 ) and sperm whales ( Farmer et al, 2018b , 2018a ).…”
Section: Marine Mammal Dynamic Bioenergetic Modellingmentioning
confidence: 99%
“…The most widespread use of dynamic bioenergetic models in the past decade has been in the context (either implicit or explicit) of assessing the long-term consequences of sublethal anthropogenic disturbance on individuals or populations under the PCoD framework, which has included applications to pinnipeds ( Goedegebuure et al, 2018 ; McHuron et al, 2017a , 2018 ), harbour porpoises Phocoena phocoena ( Gallagher et al, 2021a ; Harwood et al, 2020 ; Nabe-Nielsen et al, 2014 ; Nabe-Nielsen et al, 2018 ), delphinids ( Hin et al, 2019 ; New et al, 2013b ; Pirotta et al, 2014 ; Pirotta et al, 2015 , 2020 ; Reed et al, 2020 ; Williams et al, 2006 ), beaked whales ( New et al, 2013a ), baleen whales ( Braithwaite et al, 2015 ; Christiansen and Lusseau, 2015 ; Dunlop et al, 2021 ; Guilpin et al, 2020 ; McHuron et al, 2021 ; Pirotta et al, 2018a , 2019 , 2021 ; Riekkola et al, 2020 ; van der Hoop et al, 2017 ; Villegas-Amtmann et al, 2015 ; Villegas-Amtmann et al, 2017 ), small- to medium-sized odontocetes ( Noren et al, 2017 ) and sperm whales ( Farmer et al, 2018b , 2018a ).…”
Section: Marine Mammal Dynamic Bioenergetic Modellingmentioning
confidence: 99%
“…Because humpback whales rely on finite energy stores during migration, these behavioural changes could alter a female's energy budget, thereby reducing calf growth rates, and delay arrival at the foraging grounds [ 40 ]. When incorporated into a PCoD model, Dunlop et al [ 41 ] found that similar behavioural responses to a simulated 10-day seismic survey during peak migration had negligible effects on female body condition and population growth. However, the costs of repeated exposures may accumulate over the long migration, particularly for populations migrating along coastlines with high levels of human activity.…”
Section: Life-history Traitsmentioning
confidence: 99%
“…An understanding of where, when, how, and why marine mammals congregate and move is important when assessing direct interactions with human activities that can result in injurious or lethal impacts, such as vessel strike or fishing gear entanglement. Further, the growing body of evidence clearly indicates that an animal's behaviors, activities, or states when exposed to the pervasive array of nonlethal stressors, such as underwater noise, can affect their immediate response (e.g., McHuron et al, 2018;Pirotta et al, 2021), with cumulative exposures potentially affecting individual fitness, which may ultimately result in population-level impacts (e.g., New et al, 2014;Dunlop et al, 2021;Pirotta et al, 2022).…”
Section: Introductionmentioning
confidence: 99%